Food waste in Labuan Bajo: a baseline study of food waste in a priority tourism destination in Indonesia - Bachtiar, Eva; Nur, Alfian Muhammad; Lasmana, Grace Vanessa; Lipu, Bergita Gusti; Simamora, Hosiana; Rudyan, Peter Xandya; Panggabean, Romauli; Cholidah, Sri Noor (Frontiers in Sustainability, 2026)
Food waste is a growing environmental, nutritional, and economic concern, particularly in tourism-dependent regions. Labuan Bajo, a priority tourism destination in Indonesia, faces challenges in food waste management due to seasonal tourist influx, limited infrastructure, and reliance on outsourced food. This study aimed to comprehensively assess food waste generation, composition, destinations, recovery potential, and associated impacts across households and non-household sources, including hotels, restaurants, food stalls, cafés, traditional markets, and tourist boats. Data were collected through direct weighing, surveys, interviews, and secondary sources. The total food waste was estimated at 4,836 tons, with non-household sources contributing slightly more than households (51%). Most waste was repurposed as animal feed (58.9%), while 25.4% went to landfill and 8.7% was disposed of at sea. Edible parts accounted for over half of the waste (55%), with a notable portion recoverable for human consumption (24%). Drivers of food waste included consumer preferences, cultural habits, inadequate food management, and strict quality and safety standards. The findings highlight the substantial influence of tourism on waste generation and emphasize the potential for surplus food recovery. Evidence-based, context-specific strategies are recommended to reduce food waste, enhance food security, and support sustainable tourism in Labuan Bajo.